A Mobility-Aware Efficient Routing Scheme for Mobile Sensor Networks. (19th March 2013) - Jung, Jinman; Cho, Yookun; Hong, Jiman
In mobile sensor networks, a variety of dynamic environmental conditions affect performance. Node movement caused by the network environment or by mobile entities makes the sensors particularly vulnerable to route failures, which in turn affects the efficiency and reliability of these networks. Therefore, mobility is an important factor in the design of a routing protocol for mobile sensor networks. In this paper, we propose a mobility-aware efficient routing called MAER, in which sensor nodes make use of mobile information to select the most appropriate routing behavior. The proposed method integrates proactive and reactive routing components efficiently using a sink cluster that consists of underlying multiple static or slow sensor nodes. The cluster provides the stable paths between less mobile entities efficiently. Our scheme also uses mobile information to evaluate and select alternative paths during a route discovery process, thus allowing sensor nodes dynamically to adapt to varying mobile networks. We evaluate the performance of MAER using a simulation by comparing it to the most popular standard for WSN, AODV. The results of the simulation show that our scheme outperforms AODV in mixed mobile sensor networks.